IMPLEMENTING OF FINES IN DEFAULT OF ONLINE SALES ENTRUSTMENT CONTRACT BASED ON TA'WIDH IN THE SAMSARAH CONTRACT - Arif Hidayat (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2023)
Consigngaming and Unbranded_Store are online shops that are engaged in selling electronic goods from entrusted sellers. The operational principle of the two online shops is to mediate sellers and buyers in sales transactions of electronic and informatics products with standard agreements and conditions set by the online shop, one of the dictums of which contains provisions for fines for defaults on the seller's part. This fine is the focus of the study with the problem of how to determine the amount of the fine to the seller who violates the dictum of the Consigngaming and Unbranded_Store sales agreement, the effectiveness of applying fines to reduce the level of default on the part of the seller and review of the samsarah contract on the determination of fines for seller defaults. To meet scientific standards, the authors designed a research procedure with stages, namely a normative sociological research approach, a descriptive analytical research type with data collection techniques through interviews and documentation. The results of his research are that the determination of fines in Consigngaming is based on the percentage of the price of goods set by the seller, and the Unbranded_Store fine value is fixed which is stated in the general provisions of the transaction that the seller must comply with. The fines imposed by these two consignments, although the procedures are different, have been able to reduce the potential for sellers to commit defaults which could harm Consigngamig and Unbranded_Store management in terms of performance and branding as online stores that have credible business qualifications and can significantly reduce the level of seller defaults. Determination and imposition of fines for seller's default on both consignments as a business based on a samsarah contract is in accordance with the concept of ta'widh and the scholars allow the application of the ta'widh which is implemented based on the agreement of the parties in the consigmnet agreement (samsarah) as long as the dictum does not conflict with the provisions syara'.